Identification of H3K4me1-associated proteins at mammalian enhancers. (January 2018) - Local, Andrea; Huang, Hui; Albuquerque, Claudio; Singh, Namit; Lee, Ah; Wang, Wei; Wang, Chaochen; Hsia, Judy; Shiau, Andrew; Ge, Kai; Corbett, Kevin; Wang, Dong; et al.
Abstract Enhancers act to regulate cell-type-specific gene expression by facilitating the transcription of target genes. In mammalian cells, active or primed enhancers are commonly marked by monomethylation of histone H3 at lysine 4 (H3K4me1) in a cell-type-specific manner. Whether and how this histone modification regulates enhancer-dependent transcription programs in mammals is unclear. In this study, we conducted SILAC mass spectrometry experiments with mononucleosomes and identified multiple H3K4me1-associated proteins, including many involved in chromatin remodeling. We demonstrate that H3K4me1 augments association of the chromatin-remodeling complex BAF to enhancers in vivo and that, in vitro, H3K4me1-marked nucleosomes are more efficiently remodeled by the BAF complex. Crystal structures of the BAF component BAF45C indicate that monomethylation, but not trimethylation, is accommodated by BAF45C's H3K4-binding site. Our results suggest that H3K4me1 has an active role at enhancers by facilitating binding of the BAF complex and possibly other chromatin regulators. The authors conduct mass spectrometry experiments identifying H3K4me1-associated proteins, including members of the BAF chromatin-remodeling complex. They show that H3K4me1 augments association of the BAF complex with enhancers in vivo and that H3K4me1-marked nucleosomes are more efficiently remodeled by the BAF complex in vitro.